Revolutionizing Healthcare: Spatial Computing Meets Generative AI - Sankara Reddy Thamma, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The health industry is experiencing change, the newest forerunner of which is being propelled by spatial computing and generative AI. Spatial computing simply refers to the ability to interface with physical space through computation and digital devices; on the other hand, generative AI means using advanced machine learning to generate new output. This paper examines the roles and the combined possibilities of these two technologies with the view of transforming health care and diagnostics in the field of patient care. Precision medicine unveils new opportunities of integrating precise spatial computing components and generative artificial intelligence to provide a personalized treatment for patients and data visualization for surgeons. The paper examines major use cases, concerns, and future of this convergence specifically in the fields of medicine.
Keywords: Spatial Computing; Generative AI; Healthcare; Precision Medicine; Augmented Reality; Machine Learning; Patient Care; Digital Health; Artificial Intelligence; Health Data Visualization; Generative Adversarial Networks